Structural transformation and international trade: Evidence from the China shock - Clément Nedoncelle; Julien Wolfersberger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
How does international trade affect structural transformation in developing countries? We use data on sectoral allocation of labour and value-added in 46 developing economies over the period 1995-2017 and exploit for identification plausibly exogenous variation in manufacturing imports from China. We find that the so-called 'China shock' largely slows down the transformation of low- and middle-income economies out of agriculture. In our main specification industrialization decreases by 0.49 per cent on average for each additional per cent of manufacturing imports from China. It highlights a competition effect where exposure to Chinese imports is largely detrimental to structural transformation. These results hold across geographical regions, with a difference in Sub-Saharan Africa, where international trade causes an increase in the size of the services sector.
Keywords: F14; F63; O11; 330; developing economies; industrialization; structural transformation; trade